2018
DOI: 10.1371/journal.pone.0201571
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of linear lipopeptides derived from BP100 towards plant pathogens

Abstract: A collection of 36 lipopeptides were designed from the cecropin A-melittin hybrid peptide BP100 (H-Lys-Lys-Leu-Phe-Lys-Lys-Ile-Leu-Lys-Tyr-Leu-NH2) previously described with activity against phytopathogenic bacteria. These lipopeptides were synthesized on solid-phase and screened for their antimicrobial activity, toxicity and proteolytic stability. They incorporated a butanoyl, a hexanoyl or a lauroyl group at the N-terminus or at the side chain of a lysine residue placed at each position of the sequence. Thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 51 publications
2
36
1
Order By: Relevance
“…Some of the analogs synthesized and tested in the present work were chosen in light of the promising results obtained for them in previous studies involving human bacterial pathogens [ 30 , 32 ]. Cationic peptides have been previously found to be effective against fungal plant pathogens [ 33 , 34 ]. In the present work, the poor reactivity of Aib residues has been successfully overcome using a green [ 35 ] and cost-effective synthetic strategy to produce trichogin analogs.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the analogs synthesized and tested in the present work were chosen in light of the promising results obtained for them in previous studies involving human bacterial pathogens [ 30 , 32 ]. Cationic peptides have been previously found to be effective against fungal plant pathogens [ 33 , 34 ]. In the present work, the poor reactivity of Aib residues has been successfully overcome using a green [ 35 ] and cost-effective synthetic strategy to produce trichogin analogs.…”
Section: Introductionmentioning
confidence: 99%
“…These three genera are considered as factories for the production of biologically active molecules which are potent growth inhibitors of phytopathogens. Lipopeptides, a subclass of antimicrobial peptides, arenow emerging as an attractive alternative for the development of new peptide-based biopesticides [84,200]. The usefulness of lipopeptides is being evaluated as a potent versatile weapon for the control of a wide range of phytopathogens.…”
Section: Future Prospects Of Microbial Lipopeptides In Plant Disease mentioning
confidence: 99%
“…This confluence of factors makes research into novel efficient and sustainable strategies a priority to control Psa. Among the several innovative strategies that have been proposed as short-term alternatives to control Psa [ 27 , 28 , 29 , 30 ], namely the use of bacteriophages [ 31 ], essential oils, and plants’ metabolites [ 32 , 33 , 34 ], the antimicrobial peptides (AMPs) are probably the most consensual solution towards a more sustainable and safer agriculture [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…BP100 is one of the most tested AMPs, since Badosa et al [ 58 ] designed and demonstrated its high potential to control phytopathogenic bacteria. The bioactivity of this AMP has been demonstrated against Erwinia amylovora [ 48 ], Xyllela fastidiosa [ 51 ], Dickeya chrysanthemi [ 59 ] and also tested against Psa [ 29 ]. Due to the potential of this peptide, several analogs were designed and tested on pathogenic bacteria, such as RW-BP100 [ 60 ].…”
Section: Introductionmentioning
confidence: 99%